Finding the best operating condition in a novel process for explosive waste incineration using fluidized bed reactors. (2nd November 2020) - Cho, Sunghyun; Park, Chanho; Lee, Jiheon; Lyu, Byeongil; Moon, Il
Abstract: Explosives are among one of the most important components of a military system, and old explosives must be disposed safely and cleanly. Several explosive waste disposal methods have been developed, especially rotary kilns. Although using rotary kilns is better than other methods, problems like NOx emissions still exist. Thus a need of new and more efficient type of incinerator is required. Since fluidized bed reactors are well known for effective heat transfer and well mixed conditions, they have been proposed as an advanced incinerator. In this study, fluidized bed was simulated in CFD (computational fluid dynamics) program. The objective was finding the conditions that produced the lowest NOx emissions. By the CFD simulation, it was found that the change in inlet gas affects hot spot generation, and hot spot temperature is closely related to NOx emissions. As a result, the model was optimized through these characteristics and CFD simulation data. Graphical abstract: Image, graphical abstract